Navigating the Challenges of Digital Transformation: Insights from the Salary Payment System in Sangkat Ta Khmau - Marvin Vanny; Lince Magriasti (Faculty of Social Science, Universitas Negeri Padang, 2026)
This research seeks to investigate the problems faced by civil servants in Sangkat Ta Khmau with regards to the implementation of a digital system for salary payment. Through qualitative research, the problems faced by civil servants with regards to technological literacy, security concerns, and attitude towards change were noted as key issues affecting the success of the digital system for civil servants.